The Impact of Brand Satisfaction on Brand Loyalty Through Brand Trust among Online Ojek Customers - Utami, Budi (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This study aims to examine the impact of brand satisfaction on brand loyalty, mediated by brand trust, among online ojek customers. The main variables in this research are brand satisfaction, brand trust, and brand loyalty. Brand satisfaction is expected to build customer trust in the brand, which in turn, influences their loyalty. The research employs a quantitative approach by collecting data through a self-administered questionnaire filled out by 118 online ojek customers. The data were then analyzed using Structural Equation Modeling (SEM) with the help of Lisrel 8.8 software to test the relationships between the variables. The findings of the study reveal several key insights: first, brand satisfaction has a positive and significant effect on brand trust, meaning that the more satisfied customers are with the brand, the higher their level of trust. Second, brand satisfaction has a negative effect on brand loyalty, indicating that other factors may influence loyalty beyond satisfaction alone. Third, brand trust has a positive and significant impact on customer loyalty, highlighting the critical role of trust in fostering long-term loyalty.